Perry's Handbook Example 12-3 Video Solution - Hariri, M. Hossein (McGraw-Hill's AccessEngineering., 2011)
This video illustrates the determination of air humidity and thermodynamic properties after evaporative cooling of moist air. Fig 12-2a, Grosvenor psychrometer chart, and Fig 12-6c are used for the calculation.